Arteriovenous Malformation of the Distal Ileum in a 14-Year-Old Girl with Recurrent Abdominal Pain: A Case Report - Hyein Kang; Eun Sun Lee; Hee Sung Kim; Mi Kyung Kim; Kwi-Won Park; Dae Yong Yi; Byung Ihn Choi; Jong Beum Lee; Hyun Jeong Park (대한영상의학회지, 2018)
Arteriovenous malformation (AVM) is a lesion involving a high-flow vascular malformation, which is one of the causes of massive gastrointestinal bleeding. In the pediatric population, AVM is quite rare in the gastrointestinal tract, and the most common primary site is the colon. A small bowel is a rare primary site of AVM, and only 1 case has been reported in Korea. Here, we report on a case of AVM found in the distal ileum of a 14-year-old girl who complained about recurrent lower abdominal pain only without a gastrointestinal hemorrhage. In the previous research literature, a small bowel AVM can be diagnosed through detecting the existence of an enhancing nidus of the intestinal wall at the arterial phase, accompanied by an early draining vein as it appeared on a dynamic contrast-enhanced abdominal computed tomography. In our case, the pathologically confirmed AVM of the distal ileum showed a dot-like enhancement within the thick low-attenuating submucosal layer of the terminal ileum.